2018
DOI: 10.1080/08870446.2018.1453509
|View full text |Cite
|
Sign up to set email alerts
|

Influencing health decision-making: A study of colour and message framing

Abstract: In accordance with the Unification Theory of Framing, a match between the representations of the target behaviour, the colour prime, and the frame resulted in the greatest amount of persuasion. Creating communications with representations that match the target behaviour could be a powerful tool to increase compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Among the studies used, 5 were funded by the government or institute grant [ 22 , 23 , 25 , 26 , 38 ], 2 by the institute and the center [ 24 , 29 ], 2 by the institute and universities [ 30 , 34 ], 2 by universities [ 28 , 37 ], and 1 by the health charity and behavioral insights project [ 35 ]. The remaining 12 studies did not report receiving any funding [ 21 , 27 , 31 - 33 , 36 , 39 - 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the studies used, 5 were funded by the government or institute grant [ 22 , 23 , 25 , 26 , 38 ], 2 by the institute and the center [ 24 , 29 ], 2 by the institute and universities [ 30 , 34 ], 2 by universities [ 28 , 37 ], and 1 by the health charity and behavioral insights project [ 35 ]. The remaining 12 studies did not report receiving any funding [ 21 , 27 , 31 - 33 , 36 , 39 - 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Because some cancers are associated with a particular sex, 2 studies notably recruited all-male participants [ 32 , 42 ], while another 10 studies recruited all-female participants [ 21 , 23 , 24 , 26 , 30 , 34 , 35 , 37 , 39 , 44 ]. Also, there was a range of different cancer topics targeted during the study interventions, including 9 studies for skin cancer [ 22 , 25 , 27 , 31 , 33 , 36 , 40 , 41 , 45 ], 2 for colorectal cancer [ 28 , 38 ], and 1 for lung cancer [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite voluminous behavioral and some neurological support, a growing body of research calls into question the completeness of the traditional dual-process view of decision making (Gonzalez et al, 2005; Kruglanski et al, 2006; O'Keefe and Jensen, 2007, 2009; Kühberger and Tanner, 2010; Gigerenzer and Gaissmaier, 2011; Reyna and Brainerd, 2011; Wright et al, 2012, 2013; Mega et al, 2015; Smith et al, 2015; Van't Reit et al, 2016; Li et al, 2017; Seta et al, 2017; Voss et al, 2018). Two recent brain imaging studies, for example, reported that increased DMN activation (and/or connectivity) was related to RCFE susceptibility to a greater extent than reward related processing, contrary to the predictions of traditional dual-process theories (Smith et al, 2015; Li et al, 2017).…”
Section: Dmn Activation Affects Decision Bias In Younger Adults and Imentioning
confidence: 99%
“…The way people process health-related information is not completely rational [6,7]; this indicates that the sole examination of media presentations cannot precisely measure the real persuasive effects of messages [8,9]. People's decision-making preferences are also affected by how information is presented [10][11][12]. According to framing effect theory, different presentations of health-related information can affect individuals' decision-making preferences.…”
Section: Introductionmentioning
confidence: 99%